Hubungan Antara Mindful Parenting dengan Literasi Baca-Tulis Remaja di Kampung Cisanggarung Kecamatan Cimenyan Kabupaten Bandung Jawa Barat - Irianti Usman; Nurlaela Hamidah; Riyanda Utari; Aliza Nur Muhammad; Bunga Alodia Isfara; Yudi Hadiana Hidayat (Transformasi Manageria: Journal of Islamic Education Management, 2023)
Literacy is an inseparable part of human civilization that can help measure societal strata and how the society in a nation interpretes time development as well as how far they can survive in it. In this study, we specifically wanted to look at the relationship between Kabat-Zin mindful parenting (a conscious parenting style) and the reading and writing literacy of teenagers in Kampung Cisanggarung, Cimenyan District, Bandung Regency, West Java. This study used a quantitative research method with a correlational design. From a total population of 488, 24 adolescents aged 10-19 years old were purposively chosen from 24 families who have teenage children. The reading and writing literacy of Kampung Cisanggarung youths was measured by using the Ministry of Education and Culture literacy scale . Meanwhile, the mindful parenting pattern was investigated by using a scale derived from Duncan and Zinn’s 5 dimensions of mindful parenting. Pearson Product Moment formula was implemented to determine the magnitude of the correlation coefficient between the two variables: whether or not the relationship is significant. The correlation coefficient found was r = 0.450 with a significance probability value of 0.027 indicating that there is a significant positive correlation between mindful parenting and literacy (r = 0.450; p <0.5). Several factors were assumed to be the influential reasons for such a medium correlation level category. Parent’s low level of education may prevent adequate knowledge in parenting. Another possible cause found was lack of example given by parents to their children in the literacy aspect.